Lean Strategy Implementation to Improve Throughput in Assembly Line: Dul-Db21ssc Manufacturing Process at PT. X - Santoso, Gemma Eka; Ayu, Gita; Septivani, Nike (Bina Nusantara University, 2013)
Lean production has dramatically lifted the competitiveness of many manufacturing companies and the value they deliver to customers. This project examines the benefit of balancing process and workstation arrangement of dogbone damper in an order that maintains a smooth flow of materials and component through the process. The analysis begins from calculating takt value to establish the required rate of production. From here, any total cycle time exceeding takt time is called a bottleneck process and should become a target of the improvement. Next, arranging people and equipment into cells has great advantage in terms of achieving lean goals. One advantage of cells is the one-piece flow concept, which states that each product moves through the process one unit a time without sudden interruption, at a pace determined by the customer?s need.